Impact of cross-sectional area ratio on time-averaged pressure drop induced by jet pump for thermoacoustic engine - Tang, K (2020)
In this study, the suppression mechanism of the jet pump in oscillatory flow is investigated, and the emphasis is put on the effect of cross-sectional area ratio on the performance of jet pumps with different taper angles. An experimental apparatus has been built to measure the time-averaged pressure induced by the jet pump. When the taper angle ranges from 3° to 9°, the time-averaged pressure drop and working efficiency can be improved by increasing cross-sectional area ratio, and the change of taper angle has little effect on the performance of jet pumps. However, as the taper angle increases beyond 9°, the performance of jet pump with a large cross-sectional area ratio degrades considerably. In addition, the time-averaged pressure drops induced by the jet pumps with different cross-sectional area ratios are similar, and the taper angle becomes more dominant for jet pump’s performance.